1988
DOI: 10.2307/1130483
|View full text |Cite
|
Sign up to set email alerts
|

Infant Visual Attention in the Paired-Comparison Paradigm: Test-Retest and Attention-Performance Relations

Abstract: The visual behavior of infants in the paired-comparison paradigm was assessed with multiple discrimination tasks week-to-week at 4 and 7 months and longitudinally from 4 to 7 months. Results indicated that although task-to-task reliability was extremely variable and typically low, most measures of infants' attention averaged across multiple tasks were reliable from 1 week to the next as well as relatively stable over the longer longitudinal period. Across all groups, infants who had shorter fixations (i.e., mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
66
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(71 citation statements)
references
References 0 publications
5
66
0
Order By: Relevance
“…In this sample, they estimated correlations with IQ at 3 years of age to vary between .37 and .63 depending on the number of tasks included. Similarly, Colombo, Mitchell, and Horowitz (1988) inspected various aspects of visual attention in over 60 infants, tested several times at either about 4 or 7 months. They concluded that some aspects of visual attention (specifically, shift rate) were reliable individual features at one age tested (7 months), but not at the other one (4 months).…”
Section: Why Are the Speech Predictors No Better Than The Nonlinguistmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sample, they estimated correlations with IQ at 3 years of age to vary between .37 and .63 depending on the number of tasks included. Similarly, Colombo, Mitchell, and Horowitz (1988) inspected various aspects of visual attention in over 60 infants, tested several times at either about 4 or 7 months. They concluded that some aspects of visual attention (specifically, shift rate) were reliable individual features at one age tested (7 months), but not at the other one (4 months).…”
Section: Why Are the Speech Predictors No Better Than The Nonlinguistmentioning
confidence: 99%
“…This approach has yet to be used in infant speech perception, where participants perform either a single task (e.g., the prosody studies) or multiple tasks thought to be fundamentally different (e.g., processing native vs. nonnative sounds). The example from Colombo et al (1988) discussed earlier is worth bringing up in this context, as it illustrates how development may interfere with long-term stability. This is particularly relevant for language, as infants continue to master their native language as a function of exposure (Table 2).…”
Section: How May the Infant Speech Perception Tasks Bementioning
confidence: 99%
“…Moderate test-retest reliabilities have been reported for composites such as these over periods of one week, r = .40 and .51 (Colombo, Mitchell, & Horowitz, 1988;Rose & Feldman, 1987;Rose, Feldman, & Wallace, 1988) Recall Memory-Recall memory was assessed with two tasks, elicited imitation and symbolic play. In elicited imitation, the examiner modeled each of three event sequences (e.g., place small block on paddle, cover block, shake paddle to create rattle sound) three times in succession; after a 15-min delay, the infant was given the props for each sequence, in turn, to reproduce the sequences (Bauer, 2002;Bauer, Van Abbema, & de Haan, 1999;Bauer, Wiebe, Carver, Waters, & Nelson, 2003).…”
Section: Infant Measuresmentioning
confidence: 99%
“…When tested on the VPC task, the length of familiarization phase required for infants to exhibit novelty preferences decreases as a function of age (see Rose et al, 1982), so much so that researchers working with different age groups often use infant-controlled familiarization procedures (Diamond, 1995;Pascalis, de Haan, Nelson, & de Schonen, 1998), or design studies allowing younger infants longer familiarization times than older infants (Colombo, Mitchell, & Horowitz, 1988;Jacobs, 2000;Rose, Feldman, & Jankowski, 2001). Similarly, when tested on a deferred imitation task, 6-month olds require a demonstration period that is twice the length of that used with 12-month-old infants, in order to exhibit equivalent imitation performance after a delay (Barr, Dowden, & Hayne, 1996).…”
Section: Encodingmentioning
confidence: 99%